Community Economic Empowerment Through Baitul Maal Wat-Tamwil: A VOSviewer Bibliometric Study - Alya Farika; Tatia Nur Fauziyah; Stefania Wahyu Safitri; Fijar Rahmawan Rushady (Wealth: Journal of Islamic Banking and Finance, 2025)
This study aims to identify the developmental map of research on Community Economic Empowerment through Baitul Maal Wat Tamwil using a bibliometric analysis with VOSviewer. The research was conducted over a period of six months, from February 2025 to June 2025, by searching the OpenAlex website using the keyword Economic Empowerment. A total of 349 research articles were obtained. These articles were then analyzed descriptively, input into VOSviewer, and processed to visualize the mapping of topic and subject developments related to Economic Empowerment. The findings show that the number of publications on Economic Empowerment has increased significantly every month. Furthermore, based on the visualization results generated by VOSviewer, research on Economic Empowerment is divided into four clusters.